Pemenuhan Nafkah Keluarga dengan Suami Gangguan Mental Perspektif Iṡtisna’iyat At-Taklif - Devi, Elvira Rahma; Nashirudin, Muh (Saree: Research in Gender Studies, 2024)
This study explores the fulfillment of family needs in two households in the village of Mendak, where the husbands suffer from mental disorders and the wives have to earn a living. The study also discusses the concept of Iṡtisna’iyat At-Taklif, which exempts individuals with mental disorders from legal obligations. This field research involved interviews with these wives, neighbours, and village officials, as well as related literature studies. The results show that the wives of men with mental disorders must work to meet their family's needs, with assistance from family, neighbours, and the village government. In terms of legal capability, the husbands in this study have fluctuating legal competence depending on their conditions. These cases fall under the "awaridh ahliyyah samawi" category (obstacles arising from outside the individual), with variations in the type of their mental disorders. AbstrakPenelitian ini mengeksplorasi cara pemenuhan nafkah bagi dua keluarga di desa Mendak, di mana suami mengalami gangguan mental dan istri harus mencari nafkah. Studi ini juga membahas konsep Iṡtisna’iyat At-Taklif, yang mengecualikan orang dengan gangguan mental dari beban hukum. Penelitian lapangan ini melibatkan wawancara dengan istri-istri tersebut, tetangga, dan pejabat desa, serta studi literatur terkait. Hasilnya menunjukkan bahwa istri dari pria dengan gangguan mental harus bekerja untuk memenuhi kebutuhan keluarga, dengan bantuan dari keluarga, tetangga, dan pemerintah desa. Dalam hal kapabilitas hukum, suami dalam studi ini memiliki kecakapan hukum yang berfluktuasi tergantung pada kondisi mereka. Kasus ini termasuk dalam kategori "awaridh ahliyyah samawi" (hambatan yang timbul dari luar diri individu), dengan variasi dalam jenis gangguan mental mereka.